SMARCAD1 Phosphorylation and Ubiquitination Are Required for Resection during DNA Double-Strand Break Repair - Chakraborty, Sharmistha; Pandita, Raj K.; Hambarde, Shashank; Mattoo, Abid R.; Charaka, Vijaya; Ahmed, Kazi M.; Iyer, Swaminathan P.; Hunt, Clayton R.; Pandita, Tej K. (iScience, 2018)
The chromatin remodeling factor SMARCAD1, an SWI/SNF ATPase family member, has a role in 5′ end resection at DNA double-strand breaks (DSBs) to produce single-strand DNA (ssDNA), a critical step for subsequent checkpoint and repair factor loading to remove DNA damage. However, the mechanistic details of SMARCAD1 coupling to the DNA damage response and repair pathways remains unknown. Here we report that SMARCAD1 is recruited to DNA DSBs through an ATM-dependent process. Depletion of SMARCAD1 reduces ionizing radiation (IR)-induced repairosome foci formation and DSB repair by homologous recombination (HR). IR induces SMARCAD1 phosphorylation at a conserved T906 by ATM kinase, a modification essential for SMARCAD1 recruitment to DSBs. Interestingly, T906 phosphorylation is also important for SMARCAD1 ubiquitination by RING1 at K905. Both these post-translational modifications are critical for regulating the role of SMARCAD1 in DNA end resection, HR-mediated repair, and cell survival after DNA damage. [Display omitted] •DNA damage induces ATM-dependent phosphorylation of SMARCAD1 at T906•Ubiquitination by RING1 at K905 stabilizes SMARCAD1-pT906•SMARCAD1-pT906 and ubiquitination are necessary for DSB recruitment and DNA resection•Post-translational SMARCAD1 modifications are critical for DSB repair by HR In Vitro Toxicology Including 3D Culture; Bioengineering; Tissue Engineering